Central Africa - Agricultural trade policy debates and developments: Agritrade Executive Brief Update 2013 - Technical Centre for Agricultural and Rural Cooperation; Eastern Africa Grain Council (Technical Centre for Agricultural and Rural Cooperation, 2013)
Despite the existence of two major regional integration processes in Central Africa (CEMAC and ECCAS), intra-regional trade of food products is poorly developed, with the major trade flows being with the EU, the US and increasingly with emerging economies such as China. Central African countries have differentiated interests in the agricultural sector according to their levels of urbanisation, availability of agricultural land and level of oil wealth. Yet, a common feature in all of these countries is the insufficient level of local production to meet consumer needs, giving rise to a dependence on extra-regional imports. Despite a number of efforts at national and regional level, the region still faces food insecurity problems. This Executive Brief focuses on 2012-13 developments in the Central African agricultural sector. After analyzing the main production and trade trends of some key products (such as cereals, poultry, rice, sugar, cocoa, cotton, banana and some niche market products), it presents the recent developments on the implementation of the Comprehensive Africa Agricultural Development Programme (CAADP), the EPA and other FTA negotiations. It also highlights a few current policy debates and issues.